A new life in Israel : 1950-1954 - Redlich, Shimon, 1935- (Academic Studies Press, 2017)
""A New Life in Israel, 1950-1954" is the last book in the trilogy about Shimon Redlich's childhood and adolescence. In "Together and Apart in Brzezany" he discussed his childhood in prewar and wartime Brzezany. "Life in Transit" told the story of his adolescence in the city of Lodz in postwar Poland. "A New Life in Israel" focuses on his first years in the Jewish state. The book bears witness to the adjustment of one young immigrant--one among thousands--to the realities of a new life in Israel"-- Provided by publisher.
Keywords: Redlich, Shimon, -- 1935-; Jews, Ukrainian -- Israel -- Biography.; Holocaust survivors -- Israel -- Biography.; Israel -- Biography.; Survivants de l'Holocauste -- Israël -- Biographies.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical.; HISTORY -- Middle East -- Israel.; Holocaust survivors.; Jews, Ukrainian.; Israel.; Biographies.